Hotel profitability in Spain: Impact of the location of tourist destinations - Francisca J. Sánchez-Sánchez; Ana M. SÁNCHEZ-SÁNCHEZ (Tourism and Hospitality Management)
Purpose - This paper evaluates the impact of the location of tourist destinations on Spanish hotel profitability. For this purpose, the factors that describe tourism profitability are identified and clusters of tourist destinations are developed. The model also analyses the determinants of profitability based on location models developed in the hotel sector, such as accessibility, agglomeration, and seasonality of the tourist destination. Methodology - Multivariate analysis techniques and non-parametric contrasts are applied. Findings - The results highlight the importance of the location of tourist destinations, the preferred tourist mode, and the level of seasonality on tourist profitability. There is an economic, labour and efficiency imbalance that benefits coastal vacation destinations with lower levels of seasonality, located in the Mediterranean strip, the Balearic Islands, and the Canary Islands. Originality - Special attention is paid to factors related to the location of tourist destinations from the perspective of both supply and demand, which makes it possible to isolate and quantify the effect of the tourist destination on profitability, which is essential for good planning and management.